Come and get it : a novel [large type] - Reid, Kiley (Good morning America book club., 2024)
"It's 2017 at the University of Arkansas. Millie Cousins, a senior resident assistant, wants to graduate, get a job, and buy a house. So when Agatha Paul, a visiting professor and writer, offers Millie an easy yet unusual opportunity, she jumps at the chance. But Millie's starry-eyed hustle becomes jeopardized by odd new friends, vengeful dorm pranks, and illicit intrigue"--